Pengaruh kompetensi, independensi dan due professional care terhadap kualitas audit pada badan pengawasan keuangan dan pembangunan Provinsi Sumatera Selatan - Putri, Jauza Islamia; Yulina , Bainil; Indriasari , Desi (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2022)
This study aims to examine the effect of Competence, Independence and Due Professional Care on Audit Quality. The population in this study were all auditors at the Financial and Development Supervisory Agency (BPKP) of South Sumatra Province with a sample of 90 people. Collecting data by distributing questionnaires using a 5 (five) Likert. Data analysis used SPSS version 25. The statistical method in testing the research hypothesis was multiple linear regression analysis. The results of the study show that: (1) Competence and Due Professional Care have an effect on Audit Quality, while Independence has no effect on Audit Quality (2) Competence, Independence and Due Professional Care simultaneously affect Audit Quality at the Financial and Development Supervisory Agency (BPKP) South Sumatera Province. It can be concluded that competence and independence influence audit quality.